Athlete medicine applied in a pandemic: disparities among athletes and performers reveal the need for a true `revolution` in health care - Tucker, C.; Antoniak, K.; Edison, B. (BMJ Open Sport & Exercise Medicine, 2021)
While society watches athletes and artists on a screen during the COVID-19 pandemic, some proponents tout `normalcy` as the moment live in-action play resumes again. However, when we `see` these athletes, are we truly seeing them? Failing to understand and address athletes` adversity faced during this pandemic amidst social pressures to return to play under a preconceived notion of `normal` commoditises athletes; instead, we must humanise them while recognising additional burdens they bear amidst unmet healthcare needs. Athletes and performers represent a unique population; they stand at the intersection of racial and socioeconomic health inequity and societal expectations for entertainment. Returning to the field or stage suddenly, unscathed by effects of global viral and racial pandemics, is impossible. Instead, athletes face resuming play with a sobering realisation the pursuit of health is not fulfilled with the same tenacity for everyone. This editorial is to raise awareness to disparities that exist for athletes and performing artist athletes during the COVID-19 pandemic and beyond.